2017
DOI: 10.1371/journal.pone.0175909
|View full text |Cite
|
Sign up to set email alerts
|

Mortality is associated with inflammation, anemia, specific diseases and treatments, and molecular markers

Abstract: Lifespan is a complex trait, and longitudinal data for humans are naturally scarce. We report the results of Cox regression and Pearson correlation analyses using data of the Study of Health in Pomerania (SHIP), with mortality data of 1518 participants (113 of which died), over a time span of more than 10 years. We found that in the Cox regression model based on the Bayesian information criterion, apart from chronological age of the participant, six baseline variables were considerably associated with higher m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 87 publications
1
14
0
1
Order By: Relevance
“…The accumulation of DNA mutations, however, must be considered to be a biomarker of aging, even if the underlying processes were purely chronological, because they have deleterious consequences. In general, we can expect strong correlations between wellbeing, health and survival, but any causal links will be complex, see also [103] Is the feature easy to measure in practice? A feature should be easily measurable repeatedly, and the measurement should not influence health or survival by itself, and it should yield comparable results in human and other animal species [13]…”
Section: Predicting Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…The accumulation of DNA mutations, however, must be considered to be a biomarker of aging, even if the underlying processes were purely chronological, because they have deleterious consequences. In general, we can expect strong correlations between wellbeing, health and survival, but any causal links will be complex, see also [103] Is the feature easy to measure in practice? A feature should be easily measurable repeatedly, and the measurement should not influence health or survival by itself, and it should yield comparable results in human and other animal species [13]…”
Section: Predicting Healthmentioning
confidence: 99%
“…The accumulation of DNA mutations, however, must be considered to be a biomarker of aging, even if the underlying processes were purely chronological, because they have deleterious consequences. In general, we can expect strong correlations between wellbeing, health and survival, but any causal links will be complex, see also [103]…”
Section: Predicting Healthmentioning
confidence: 99%
“…An important aspect of studies about healthy aging involves the relationship between inflammation, aging, and mortality. Although studies have identified a link between inflammation and aging, the causative and correlative aspects of this link have been more difficult to determine [ 12 , 13 ]. What has been clearly identified, however, is that increases in inflammatory markers are associated with the presence of chronic diseases, such as arthritis, gout, and diabetes, as well as with the presence of acute disease [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although most recent paleopathology studies focus on specific frailty indicators that have clear statistical relationships with age-at-death [ 21 ], our study takes a global approach, considering the relationship between age-at-death and the number of lesions observed in macro-level categories. Our justification for making this globalized comparison rests in correlations that have been demonstrated between inflammation, chronic disease, aging, and mortality [ 12 , 13 ]: we therefore took into account multiple potential sources of pathology in examining the relationship between lesion accumulation and age, including those that might not seem to have immediate bearing on cause of death (i.e., congenital factors). We had two goals in carrying out this study: first, to analyze the correlation between age-at-death and the number of lesions observed, using two different methods of analysis, and second, to characterize potential differences in lesion identification using osteological and radiological analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Other potential emergent physiological processes related to aging include inflamm-aging (11,20) and metabolic syndrome (10,21). A separate subsequent study using a different human dataset and different methods independently recovered a set of biomarkers aligned with integrated albunemia as predictors of mortality (22). Thus, integrated albunemia seems promising as an emergent physiological process associated with aging and risk of mortality, but further studies are needed to establish its wider implications.…”
mentioning
confidence: 99%